Estudos sobre o uso de NbCl5 como ácido de Lewis em reações de Povarov - Silva Filho, Luiz Carlos da [UNESP]; Frenhe, Mayara [UNESP] (My University, 2011)
The aim of this work was to investigate the use of NbCl5 as Lewis acid in cycloadittion reactions [Reaction Aza-Diels-Alder (Povarov)] between Schiff bases and enol ethers. Comparison of reaction yields, obtained products as well as reaction time with NbCl5 were also a key point on this work. In the aza-Diels-Alder reactions between Schiff bases and enol ethers (dihydropyran or dihydrofuran), the NbCl5 was an excellent catalyst for the synthesis of pyrano- and furanoquinoline derivatives. These derivatives are an important class of natural products that exhibit wide range of biological activity. The reactions were carried out at low concentration of niobium and in relatively short times, resulting in yields varying from 78 to 95%.
Keywords: Niobium pentachloride; Povarov reactions; Tetrahydroquinoline derivatives; Aza-Diels-Alder reactions